As Interaçoes em sala de aula. As prácticas pedagógicas e as possibilidades de aprendizagem - Barboza Tortella, Jussara Cristina; Marting Tassoni, Elvira Cristina; Andrade Megid, Maria Auxiliadora Bueno (Diálogos Latinoamericanos, 2014)
This article aims to discuss the interactions between teachers and students in the learning processes by presenting three researches developed in different school contexts: one of them focuses on the friendly relationships developed at school and their contribution to children’s learning; the second one discusses the interactions between students and teachers, emphasizing the mediation; and the third one explores the learning environment in which school staff feels they produce disciplinary knowledge and are able to teach. For the three investigations, it was possible to consider the importance of respect towards students and the possibilities of listening to their uneasiness. The article depicts the importance of reflecting on how different actions in the classroom can promote learning when respect is established, which indicates the possibility of protecting the democratization of knowledge in this environment.